2018
DOI: 10.3390/ijms19123743
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Pathway Governs a Full Program for Dopaminergic Neuron Survival, Neurorescue and Regeneration in the MPTP Mouse Model of Parkinson’s Disease

Abstract: Wingless-type mouse mammary tumor virus (MMTV) integration site (Wnt) signaling is one of the most critical pathways in developing and adult tissues. In the brain, Wnt signaling contributes to different neurodevelopmental aspects ranging from differentiation to axonal extension, synapse formation, neurogenesis, and neuroprotection. Canonical Wnt signaling is mediated mainly by the multifunctional β-catenin protein which is a potent co-activator of transcription factors such as lymphoid enhancer factor (LEF) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 159 publications
(641 reference statements)
6
78
0
Order By: Relevance
“…The authors showed a significant increase in the SVZ-derived NSCs of the third ventricle (3V) and Aq-surrounding regions. Hence, the SN newborn DAergic neurons were mainly derived from the migration and differentiation of the NSCs in the SVZ of 3V-and Aq-adjacent regions (Xie et al, 2017), thus supporting our indication that quiescent neuroprogenitors of mNSCs can be activated not only in vitro (L'Episcopo et al, 2011c), but more importantly, in vivo, upon SNpc-DAergic lesions with PD neurotoxins (L'Episcopo et al, 2014b).After our first studies demonstrating dysregulated WβCsignalling in the MPTP mouse model of PD, both in vivo and in vitro(L'Episcopo et al, 2011a;b), more recent reports corroborated the key role of WβC in the physiopathology of PD (seeMarchetti, 2018…”
supporting
confidence: 78%
See 4 more Smart Citations
“…The authors showed a significant increase in the SVZ-derived NSCs of the third ventricle (3V) and Aq-surrounding regions. Hence, the SN newborn DAergic neurons were mainly derived from the migration and differentiation of the NSCs in the SVZ of 3V-and Aq-adjacent regions (Xie et al, 2017), thus supporting our indication that quiescent neuroprogenitors of mNSCs can be activated not only in vitro (L'Episcopo et al, 2011c), but more importantly, in vivo, upon SNpc-DAergic lesions with PD neurotoxins (L'Episcopo et al, 2014b).After our first studies demonstrating dysregulated WβCsignalling in the MPTP mouse model of PD, both in vivo and in vitro(L'Episcopo et al, 2011a;b), more recent reports corroborated the key role of WβC in the physiopathology of PD (seeMarchetti, 2018…”
supporting
confidence: 78%
“…After our first studies demonstrating dysregulated WβC‐signalling in the MPTP mouse model of PD, both in vivo and in vitro (L'Episcopo et al, ;b), more recent reports corroborated the key role of WβC in the physiopathology of PD (see Marchetti, for an up‐to‐date review). Among others, Singh, Mishra, Bharti, et al () used short hairpin (sh)RNA‐lentiviruses to genetically knockdown AXIN2 to up‐regulate WβC‐signalling in the SNpc, in 6‐OHDA‐induced parkinsonism rats.…”
Section: Therapeutic Modulation Of Wnt/β‐catenin Signallingmentioning
confidence: 82%
See 3 more Smart Citations